(untitled) (Mustansiria Dental Journal, 2004)
This study was conducted to evaluate the apical seal after lateral compaction with three types of spreaders thirty mesial canals of mandibular molars were prepared using the step-back technique and laterally condensed with gutta-percha and ZOE sealer. The roots were classified into three groups (I, II, III) and obturated as follows: group (1) was obturated with hand spreaders (ISO#30).Group (Il) was obturated with stainless steel finger spreaders Group (III) was obturated with nickel titanium finger spreaders. After 48 hours ni na incubator, the roots were coated with wt o layers of nail polish followed by one layer of sticky wax and were then submerged in 2% methylene blue. The roots were then split longitudinally and the apical leakage measured and compared for each group. The result showed that group I (with nickel titanium finger spreaders) has statistically the lowest mean of dye penetration followed by group (with stainless steel finger spreaders).Group I(with hand spreaders) showed the highest mean of dye penetration.